2015
DOI: 10.1073/pnas.1513348112
|View full text |Cite
|
Sign up to set email alerts
|

Direct mapping of local director field of nematic liquid crystals at the nanoscale

Abstract: Liquid crystals (LCs), owing to their anisotropy in molecular ordering, are of wide interest in both the display industry and soft matter as a route to more sophisticated optical objects, to direct phase separation, and to facilitate colloidal assemblies. However, it remains challenging to directly probe the molecular-scale organization of nonglassy nematic LC molecules without altering the LC directors. We design and synthesize a new type of nematic liquid crystal monomer (LCM) system with strong dipole-dipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 53 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…2(d). This configuration was observed in other LC/colloidal systems with similar geometries [15,22,23].…”
Section: A Wide Groovessupporting
confidence: 80%
“…2(d). This configuration was observed in other LC/colloidal systems with similar geometries [15,22,23].…”
Section: A Wide Groovessupporting
confidence: 80%
“…Figure 4d,e shows the magnified view of the disclination ring at the bubble boundary.Itwas apparent that the line defect formed ad omain wall between the two adjacent regions,w ith the structure considerably isotropic, that was,within the topological defect the orientational order was substantially lower than in the bulk of liquid crystal phase. [16] This showed that there existed ap hase transition during the evaporation process,f rom an ematic bubble surface to an isotropic state of the bubble boundary.O nt he other hand, in the bubble-free region, al arge area of longrange helical structure with rod-like textures was observed, along with ad irector that anticlockwise twisted (see Figure 4f;S upporting Information, Figure S10, S11). [8a] This suggested astructure transition between the bubble boundary and bubble-free region, with the CNC ordering changing from an isotropic to ac hiral nematic arrangement.…”
Section: Angewandte Chemiementioning
confidence: 97%
“…This sparse knowledge of the phase behavior and dynamics of ChLCs in confinement contrasts the one of achiral mesogens. The miniaturization trends in electronics and optoelectronics, but also the general goal to manipulate and understand matter at the nanoscale has motivated detailed studies of the structural, dynamical and thermodynamical properties of confined and semiconfined achiral mesogens. , Despite recent experimental advancements to directly probe orientational order parameter profiles in the proximity of planar, solid walls, achieving the spatial (and temporal) resolution necessary to rigorously explore these phenomenologies at the nanoscale remains experimentally extremely demanding. Still, it could be revealed that both the collective orientational (I–N) and the translational (Sm–I or Sm–N) transitions are significantly affected by finite size and interfacial (solid–liquid or liquid–liquid) interactions introduced by confining walls or the geometrical constraints in nanoporous media. , …”
Section: Introductionmentioning
confidence: 99%